Enzyme Assay in Microsomes Below Zero Degrees - Debey, Pascale (1973)
Reactions of a membrane-bound multienzyme complex (electron-transport chain of rat-liver microsomes) suspended in aqueous-organic solvent used as antifreeze at temperatures below 0° were studied. In the presence of a relatively high concentration of ethylene glycol, electron transfer can still be observed and some individual and sequential enzyme assays can be performed over a wide range of temperatures below 0°.